Asuhan Keperawatan Keluarga Tahap Perkembangan Usia Lanjut Dengan Terapi Pemberian Jus Mentimun Untuk Menurunkan Tekanan Darah Pada Ny. B - Winda Hastuti; Alfika Safitri; Rina Puspita Sari (Pusat Riset dan Inovasi Nasional, 2023)
Background: Hypertension is called the Silent Killer or something that can secretly cause the sudden death of sufferers. High blood pressure, if not controlled, can cause complications. The purpose of this study was to find out about Family Nursing Care for the Advanced Age Development Stage with Cucumber Juice Giving Therapy to Lower Blood Pressure in Mrs. B. Method: This study uses interviews and conducts an assessment of nursing care using cucumber juice non-pharmacological therapy. Results: The case study was obtained after the client was given non-pharmacological medicine of cucumber juice for four days; it was found that blood pressure decreased quite well, BP from 170/90 mmHg to 127/83 mmHg and the pain scale decreased enough from S: 6 to S: 2. Conclusion: non-pharmacological therapy giving cucumber juice given to clients is proven to be effective for lowering blood pressure. This can be seen from changes in the evaluation of the client's blood pressure results which show a change in BP from 170/90 mmHg to 127/83.